Arabic Language Learning through Musicalization, Drama, and Sholawat in Fostering Religious Muslim Intellectuals at UIN Maliki Malang and UII Dalwa Pasuruan - Ahmad Nurcholis; Bobby Rachman Santoso; Rizqiyana Hendi Rahmawati; Dhea Syahzana Sahreebanu (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2025)
This study analyzes the model of Arabic language learning through poetry musicalization, drama performance, and shalawat-based artistic practices in fostering religious Muslim intellectuals at UIN Maulana Malik Ibrahim Malang and UII Dalwa Pasuruan. Using a qualitative multiple-case study design, the research involved students, lecturers, santri, and pesantren leaders. Data were collected through observations, interviews, and document analysis, and were analyzed thematically. The findings reveal that the three artistic media serve distinct yet complementary pedagogical functions. At UIN Maliki, musicalization and Arabic drama enhance linguistic competence, public speaking, creativity, and digital literacy. At UII Dalwa,shalawat performances and traditional drama (tamthīliyyāt) strengthen religious identity, emotional engagement, and the preservation of pesantren cultural traditions. Across both institutions, these practices contribute to the formation of religious Muslim intellectuals, defined in this study as learners who integrate Arabic linguistic proficiency with Islamic ethical values, spiritual discipline, and cultural-literary appreciation. Theoretically, this study enriches holistic learning discourse by integrating cognitive, affective, psychomotor, cultural, and spiritual dimensions. Practically, it offers an integrative model that connects artistic performance with Arabic language mastery and character formation in both modern higher education and traditional pesantren environments